Penerimaan Diri Warga Binaan Rutan Kelas IIB Kudus - Aprilia Ni'mah Akasah; M. Widjanarko (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the aspects that influence the self-acceptance of the inmates of the Class IIB Kudus Detention Center. The method used in this research is a qualitative approach. Data collection in qualitative research is carried out using observation and interview methods. The conclusions of this research are (1) In the first aspect, both Informants I, II and III have the same feelings, namely they realize that they made a mistake, informants I and III have changes in their self-confidence and changes in their quieter attitude. This is different from informant II who still has self-confidence. (2) In the second aspect, both informants I, II and III have feelings of sadness and regret for what has happened in their lives and feel that their lives will be more difficult (3) In the third aspect, both informants I, II and III do not has thoughts of ruining his life in detention (4) In the fourth aspect, both informants I, II and III feel ashamed and have difficulty accepting their status (5) In the fifth aspect, both informants I, II and III have the similarity that there is regret and rejects the reality of his life, (6) In the sixth aspect, both informants I, II and III are aware of their limitations, which have advantages as well as disadvantages. (7) In the seventh aspect, informants II and III have feelings of revenge towards someone who sent him to prison. And informants I, II and III felt a feeling of injustice in their lives.